Conceptual development of paediatric vision questionnaire for opportunistic screening in optometry and ophthalmology clinics / Ai-Hong Chen, Nurul Farhana Abu Bakar and Nathan Congdon - Chen, Ai-Hong; Abu Bakar, Nurul Farhana; Congdon, Nathan (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Vision screening in children advocates preventive eye health care. Current paediatric vision screening programs have limitations due to the type of test used, inter-examiner variation, and reliability of physical testing responses that affect the accuracy of vision testing. This study aims to report the development and conceptual framework of a new questionnaire-based complementary paediatric vision screening technique. A multi-perspective development strategy was employed to integrate viewpoints from stakeholders in crafting the minimalism notion. The process of the development included item generation, item construct analysis, and conceptual model depiction. Proxy-reporting paediatric eye screening questionnaire (PRePESQ) contains four unique features: short (< ten minutes); simple (two-tier system of screening-probing layers with wording-image in answer options); wide-ranging eye screening (ocular health, physical, physiological, and perceptual vision); all-inclusive paediatric age range (from new-born to adolescent). PRePESQ is designed as a complementary paediatric vision screening adjunct to equipment-based vision screening when the apparatus required for practical paediatric vision screening is inadequate. Nurses or clinic assistants can administer at optometry and ophthalmology clinics with the assistance of primary caretakers to screen for vision disorders. Besides keeping consistency across individuals for paediatric vision screening, it also saves time and cost.